Evaluation of clinical characteristics and treatment data of acute ischemic stroke patients follow-up in a stroke center with a retrospective cohort study: Two-years analysis - Akalin, Yahya; Çakmak, Erkan; Gözel, Nevzat; Taşcı, İrem (Tokat Gaziosmanpasa University, 2024)
Objective: It was aimed to examine the clinical features and treatment aspects of the patients who were hospitalized and treated with the diagnosis of ischemic stroke in the stroke center of our hospital. Materials and Methods: This study was conducted by retrospectively analyzing the information recorded with standard data forms of inpatients treated in our stroke center between March 1, 2019 and March 1, 2021. Findings: Of the 125 patients in the study, 56.8% were female and 43.2% were male. The most common risk factor detected in patients was Hypertension. 76% of the patients were using at least one drug for thromboembolism prophylaxis. The anterior part of the brain was affected in 72.8% and the posterior part in 27.2% of the patients. Symptom onset to door time was 180 minutes or less in 84.8% of the patients and door-to-needle time average: calculated as 52 minutes. 71 patients only i.v. tPA treatment, 42 patients both i.v. tPA and mechanical thrombectomy were applied, and only mechanical thrombectomy was applied to 12 patients. The average length of stay in the intensive care unit was 9 days, with an average of 8.6 days for women and 9.4 days for men. The need for a mechanical ventilator developed in 39 patients. Death occurred in a total of 26 patients, including 16 female patients and 10 male patients. Conclusion: The incidence of ischemic stroke has been steadily increasing over the years. In order to avoid delays in the initiation of thrombolytic therapy in these patients, the number of stroke centers should be increased rapidly in our country.

Amaç: Hastanemiz inme merkezinde iskemik inme tanısıyla yatıp tedavisi yapılan hastaların klinik özellikleri ve tedavi açısından incelenmeleri amaçlandı. Gereç ve Yöntem: Bu çalışma 1 Mart 2019 -1 Mart 2021 tarihleri arasında inme merkezimizde yatarak tedavi edilen hastaların standart veri formları ile kayıt altına alınmış olan bilgileri retrospektif olarak analiz edilerek yapılmıştır. Bulgular: Çalışmada yer alan 125 hastanın %56,8’ i kadın, %43.2’ si erkek idi. Hastalarda en sık tespit edilen risk faktörü hipertansiyondu. Hastaların %76’ sı tromboemboli profilaksisine yönelik en az bir ilaç kullanmaktaydı. Hastaların %72,8’ de anterior dolaşım alanı, %27,2’ de ise posterior dolaşım alanı etkilenmişti. Hastaların %84,8’ inde semptom-kapı zamanı 180 dk ve daha kısa idi, kapı-iğne zamanı ortalama 52 dk olarak hesaplandı. 71 hastaya sadece i.v. tPA tedavisi, 42 hastaya hem i.v. tPA hem de mekanik trombektomi uygulanmış, 12 hastaya ise sadece mekanik trombektomi uygulaması yapılmıştı. Hastaların yoğun bakımda kalış süreleri ortalama 9 gün olup kadınlarda ortalama 8,6 gün, erkeklerde ise 9,4 gün olarak tespit edildi. 39 hastada mekanik ventilasyon ihtiyacı gelişti. 16’sı kadın, 10’ u erkek hasta olmak üzere toplam 26 hastada ölüm gerçekleşti. Sonuç: İskemik inme insidansı yıllar içerisinde sürekli artmaktadır. Bu hastalarda trombolitik tedavi başlanmasında gecikmeler olmaması için ülkemizde inme merkezi sayılarının hızla arttırılması gerekmektedir.
İnme Merkezinde Takip Edilen Hastaların Klinik Özelliklerinin ve Tedavi Verilerinin Retrospektif Kohort Çalışması ile Değerlendirilmesi : İki Yıllık Analiz
Keywords: Neurology and Neuromuscular Diseases; Nöroloji ve Nöromüsküler Hastalıklar